PTH-002 The yield of pathology from diagnostic flexible sigmoidoscopy in patients under 40yrs. (22nd June 2015) - Orchard, P; Rashid, M; Thorn, C; Alexander, R
Abstract : Introduction: Flexible sigmoidoscopy (FS) allows both macroscopic and histological assessment of the left colon and rectum. Current guidelines define the need for FS in patients over 40 yrs, but is lacking in those under 40 yrs. Method: Data was analysed from our prospectively collected database over a 1 year period (April 2013–14). Patients undergoing diagnostic FS under 40ys were included (n = 136). Fisher's exact and Chi squared were used for analysis. Results: 38 patients (28%) yielded pathology; 29 (21%) had a colitis, 5 (4%) had polyps, and 4 patients had other benign pathology. No patients had a cancer. Analysis of indication for FS, indicated a non-significant (p = 0.09) propensity of finding pathology in patients with rectal bleeding and abdo pain or change of bowel habit (46%). Our data supports a smaller published series (Mittapalli et al 2008) for pathology yield (p = 0.33). Conclusion: This study provides evidence that FS in the under 40's identifies pathology in approximately 1 in 4 patients. Presenting with a PR bleed in addition to other symptoms is, perhaps more likely to yield pathology. Disclosure of interest: None Declared.